Do Global Uncertainty Indices Predict Corporate Bankruptcy Risk? Evidence from Indonesian Listed Firms - Bryan Habib Gautama; Rosmita Rasyid (Politeknik Siber Cerdika Internasional, 2026)
Background: Increasing global shocks threaten corporate financial stability, particularly in emerging markets. This study measures uncertainty using the World Uncertainty Index (WUI), World Pandemic Uncertainty Index (WPUI), Climate Policy Uncertainty (CPU), and Economic Policy Uncertainty (EPU) across current, lag-1, and lag-2 periods. Bankruptcy risk is proxied by the Altman Z-Score and Distance-to-Default (DTD). Objective: This study examines the effect of global uncertainty on the bankruptcy risk of companies listed on the Indonesia Stock Exchange. Methods: Secondary data from 2000–2024 were analyzed using fixed-effects panel regression in STATA 17. Purposive sampling produced 9,377 firm-year observations for the Z-Score model and 9,156 for the DTD model. Results: EPU and CPU significantly reduced Z-Scores across all time specifications, indicating increased financial distress through an aggravation effect. WPUI had a significant negative effect at lag 2, while WUI was insignificant. In the DTD model, only current-period EPU had a significant negative effect. State-owned enterprises and the Commodity and Cyclical sectors were most vulnerable, whereas the Defensive sector was most resilient. Conclusion: Global uncertainty affects bankruptcy risk heterogeneously. The findings support sector-specific risk mitigation, strategic portfolio allocation, and stronger corporate financial resilience.